Existence of Sundanese Manuscripts as a Form of Intellectual Tradition in the Ciletuh Geopark Area - Darsa, Undang Ahmad; Sumarlina, Elis Suryani Nani; Permana, Rangga Saptya Mohamad (SCAD Independent, 2020)
The variety of Sundanese manuscripts are still scattered in individual communities, as well as those already stored in various libraries and museums in West Java. The Sundanese script is still stored in the Ciletuh Geopark, Sukabumi District. This research is interesting because of the discovery of several manuscripts around the southern Sukabumi area, especially at Surade, Ciemas, and Jampang Kulon areas. Descriptive method of comparative analysis that was used trying to describe the data in detail and thoroughly, analyze it carefully, and compare those target accurately between several texts studied. While the method of the study in the form of text critique method, referred to the method of a single script, through the standard edition. The method of content review used the method of cultural studies, which reveals the existence and function of the script pragmatically in the community, especially in the Ciletuh Geopark. The results of the research can be considered as